Pengaruh Kepemimpinan dan Motivasi terhadap Disiplin Kerja Pegawai Dinas Tenaga Kerja dan Transmigrasi Kabupaten Bima - Awalunisa, Arum; Yusuf, Muhammad; Widakdo, Sugeng (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to determine the influence of leadership and motivation on employee work discipline. The sample in this research was .47 ASN using a purposive sampling technique. Data collection techniques using observation, questionnaires and literature study. The data analysis technique uses multiple linear regression assisted by SPSS for widows. The results of the research show that leadership and motivation have a significant effect on the work discipline of employees of the Bima Regency Manpower and Transmigration Service.